Letaifu’l-i’lam fi işareti ehli’l-ilham adlı tasavvuf terimleri sözlüğü ve mütercimi mechul tercümesi - Alkan, Ercan (My University, 2002)
Sûfî müellifler kendilerine has bir takım öncüllerden hareket etmek suretiyle irfânî bir dil geliştirmişlerdir. Bu dilin oluşum sürecinde ise en büyük ve en önemli katkı, Ekberî mekteb müellifleri tarafından olmuştur. Çalışmamızı teşkil eden Letâifu'l-i'lâm fî işâreti ehli'l-ilhâm adlı eser; özelde Ekberî mektebe ait kavramların yer aldığı tasavvuf terimlerini ihtiva etmektedir. Eser 13./ 14 yüzyılda kaleme alınmıştır. Türleri içinde kapsamlı ve geniş içeriğinden ötürü dikkate şayan bir yönü vardır. Çalışma giriş ve iki bölümden oluşmaktadır. Giriş bölümünde ıstılahâtu's-sûfiyye'nin gelişim süreci ve tasavvuf ıstılahlarını ele alan başlıca eserlere kısaca değinilmiştir. Birinci bölümde, eserin Türkiye kütüphanelerindeki yazma nüshaları ve eserde zikri geçen telifat belirtilmiştir. Eserin yazılış sebebi ve eser kendisine nisbet edilen müellif sûfiler hakkında bilgi verilmiştir. İkinci bölümde ise, Süleymâniye Kütüphanesi Lala İsmail bölümü 122 numarada kayıtlı Letâifu'l-i'ilâm'ın tercüme nüshasını günümüz harflerine aktardık. Metin içerisinde geçen âyet ve hadislerin kaynakları ayrıca tespit edilmiştir.

Sufi authors have developed a mystical language by inferring from sui generis premises. The main and the most significant contribution within the evolution process of the language, is made by scholars in Akbarian School. The Lata'if Al-Ilam, a major work on Sufi terminology, reveals a deep familiarity with Sufi literary tradition, in general, and with akbarian teaching, in particular. Its author conveys Ibn Arabi's doctrine in a highly perceptive manner, presenting us with elaborate, mature and methodical thought which is nevertheless founded on inspiration, and is therefore open, dynamic and non-reductive, as is appropriate to a language of symbolic allusion and to sciences deriving from mystical experience. This study is consisting of two parts. In introduction part, the description and evolution of Sufi technical terms are mentioned. In the first part, the manuscript of this book in libraries in Turkey and the books mentioned in Lata'if Al-Ilam are cited. The brief information regarding the reason behind writing this book and author Sufis who have been erroneously attributed is given. In the second part, we translated the translated copy of Lata'if Al-Ilam from Arabic to Ottoman language, registered in number 122 in the department of Lala Ismail in Suleymaniye library, into latin words. The references of verses and hadiths in the text are determined.
Keywords: Akâid ve Kelâm; Din; Islam Dini-tasavvuf; İslam Dini; Tasavvuf Edebiyatı